A Bacteriophage Lambda-Based Genetic Screen for Characterization of the Activity and Phenotype of the Human Immunodeficiency Virus Type 1 Protease - Martínez, Miguel-Angel (American Society for Microbiology, 2000)
Human immunodeficiency virus type 1 (HIV-1) resistance to antiretroviral drugs is the main cause of patient treatment failure. Despite the problems associated with interpretation of HIV-1 resistance testing, resistance monitoring should help in the rational design of initial or rescue antiretroviral therapies. It has previously been shown that the activity of the HIV-1 protease can be monitored by using a bacteriophage lambda-based genetic assay. This genetic screening system is based on the bacteriophage lambda regulatory circuit in which the viral repressor cI is specifically cleaved to initiate the lysogenic to lytic switch. We have adapted this simple lambda-based genetic assay for the analysis of the activities and phenotypes of different HIV-1 proteases. Lambda phages that encode HIV-1 proteases either from laboratory strains (strain HXB2) or from clinical samples are inhibited in a dose-dependent manner by the HIV-1 protease inhibitors indinavir, ritonavir, saquinavir, and nelfinavir. Distinct susceptibilities to different drugs were also detected among phages that encode HIV-1 proteases carrying different resistance mutations, further demonstrating the specificity of this assay. Differences in proteolytic processing activity can also be directly monitored with this genetic screen system since two phage populations compete in culture with each other until one phage outgrows the other. In summary, we present here a simple, safe, and rapid genetic screening system that may be used to predict the activities and phenotypes of HIV-1 proteases in the course of viral infection and antiretroviral therapy. This assay responds appropriately to well-known HIV-1 protease inhibitors and can be used to search for new protease inhibitors.